James Baldwin and the 1980s : witnessing the Reagan era - Vogel, Joseph, 1981- (Urbana : University of Illinois Press, 2018)
By the 1980s, critics and the public alike considered James Baldwin irrelevant. Yet Baldwin remained an important, prolific writer until his death in 1987. Indeed, his work throughout the decade pushed him into new areas, in particular an expanded interest in the social and psychological consequences of popular culture and mass media. Joseph Vogel offers the first in-depth look at Baldwin's dynamic final decade of work. Delving into the writer's creative endeavours, crucial essays and articles, and the impassioned polemic 'The Evidence of Things Not Seen, ' Vogel finds Baldwin as prescient and fearless as ever. Baldwin's sustained grappling with 'the great transforming energy' of mass culture revealed his gifts for media and cultural criticism.
The price of the beat: Black popular music and the crossover dream -- Freaks in the Reagan era: Androgyny and the American ideal of manhood -- The welcome table: Intimacy, AIDS, and love -- "To crush the serpent": The religious right and the moral minority -- Things not seen: Covering tragedy, from the terror in Atlanta to Black Lives Matter.
Includes bibliographical references and index.
Description based on print version record.
WorldCat record variable field(s) change: 050, 082
Keywords: Baldwin, James, -- 1924-1987 -- Criticism and interpretation; Baldwin, James, -- 1924-1987; Literature and society -- United States -- History -- 20th century; American literature -- African American authors -- History and criticism; African Americans -- Intellectual life -- 20th century; Nineteen eighties; LITERARY CRITICISM -- American -- General; SOCIAL SCIENCE -- General; African Americans -- Intellectual life; American literature -- African American authors; Literature and society; Nineteen eighties; United States; 1900-1999; Electronic books; Criticism, interpretation, etc; History